Customer accounts reconciliation of Holcim Cement Bangladesh Ltd : a concentrated work on credit reconciliation - Khan, Md. Shoeb (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.